Science and technology policies in open economies : the case of Latin America and the Caribbean - Cimoli, Mario (CEPAL SantiagoCL, 2005)
Focuses on technology policy in Latin America and the Caribbean. Identifies changes in the industrial structure, institutions and technology policies in the context of open economies. Analyses market and non-market mechanisms and supply-side and demand-side incentives responsible for technical change and innovation, in order to identify technology policy opportunities for the region. Expresses the need for pragmatism and coordination in technology policy.